IMPLEMENTASI KEBIJAKAN PEMERINTAH DAERAH DALAM PELAYANAN PEMBUATAN KARTU KELUARGA (Suatu Studi di Dinas Kependudukan Dan Pencatatan Sipil Kota Padang) - Emi Handrina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
Implementation of public service is a state effort to fulfill the basic needs and civil rights of every citizen and the state of the goods, services and administrative services provided by the delivery of public services. The nature of public services is the provision of excellent service to the community which is the embodiment of the obligations of the government apparatus as a public servant. Therefore, the development of public services, namely: the institutional elements of service, process pelyanan and human resources service providers. In this connection, efforts to improve the performance of public services are always pleased with the development of these three basic elements. Improving the quality of public services is one of the agenda of bureaucratic reform, which dotted the fact of bad factual quality of public services largely determined by the quality of attitudes and character of the apparatus government that is not praised, corrupt and irresponsible. Currently, many phenomena that occur in the community that shows that the services provided by the government apparatus has not touched directly to the public interest because the system is not effective and efficient so that slow the public service and have no certainty. Just as if we take care of a file in this case about the making of family cards and other affairs often found the treatment is not good and is characterized by indifferent government apparatus so impressed slow in providing services, of course in the community in the city of Padang, it can not be allowed to take place continue, because the dynamics of community life that continues to occur also need the ideal government figure to meet the expectations of society.